Disparities in treatment patterns and outcomes among younger and older adults with newly diagnosed multiple myeloma: A population-based study. Issue 4 (May 2021) - Mian, Hira S.; Seow, Hsien; Wildes, Tanya M.; Kouroukis, C. Tom; Pond, Gregory R.; Sivapathasundaram, Branavan; Sussman, Jonathan
Abstract: Introduction: Multiple myeloma, a cancer of older adults, has seen significant improvement in therapeutic options over the past two decades. Uncovering disparities in treatment patterns and outcomes is imperative in order to ensure older adults, who are underrepresented in clinical trials, are benefitting from these advances. Methods: Adults with newly diagnosed multiple myeloma (NDMM) were identified using linked provincial administrative databases between 2007 and 2017 in Ontario, Canada. Trends in rate of no treatment, novel drug and autologous stem cell transplant (ASCT) usage was evaluated within one year following diagnosis along with the associated early mortality (<12 months) for the aforementioned cohorts among younger (≤65 years) and older adults (>65 years) with NDMM. Results: A total of 8841 adults with NDMM were identified. Rates of no treatment decreased in both age groups during the study period; however still remain considerably high among older patients (from 34.9% in 2007 to 27.4% in 2017) with high associated early mortality in the older untreated group (54.1% 1 yr mortality over study period). Despite increased usage of novel drugs in both age groups, early mortality decreased among younger patients utilizing novel drugs (16.1% to 5.6%) but remained high and stagnant in older patients using novel drugs (18.2% 1 yr mortality over study period). ASCT utilization increased in both age groups during the study period with decreasing early mortality among older patients undergoing ASCT (from 26.3% in 2007 to 1.1% in 2017). Conclusion: While several improvements have been made, rates of no treatment and early mortality among patients not treated and those started on novel drugs remains a concern in older adults with NDMM.